Imbalance Between Bone Morphogenetic Protein 2 and Noggin Induces Abnormal Osteogenic Differentiation of Mesenchymal Stem Cells in Ankylosing Spondylitis. Issue 2 (February 2016) - Xie, Zhongyu; Wang, Peng; Li, Yuxi; Deng, Wen; Zhang, Xin; Su, Hongjun; Li, Deng; Wu, Yanfeng; Shen, Huiyong
Abstract : Objective: To study the osteogenic differentiation capacity of bone marrow–derived mesenchymal stem cells (BM‐MSCs) from patients with ankylosing spondylitis (AS) and to investigate the mechanisms of abnormal osteogenic differentiation of BM‐MSCs in AS. Methods: BM‐MSCs from healthy donors (HD‐MSCs) and patients with AS (AS‐MSCs) were cultured in osteogenic differentiation medium for 0–21 days, after which their osteogenic differentiation capacity was determined using alizarin red S and alkaline phosphatase assays. Gene expression levels of osteoblastic markers and related cytokines were detected by high‐throughput quantitative reverse transcription–polymerase chain reaction. Enzyme‐linked immunosorbent assay was performed to detect protein levels of bone morphogenetic protein 2 (BMP‐2) and Noggin in the cell culture supernatant. The activation of Smad1/5/8 and MAPK signaling pathways was measured by Western blotting. The balance between BMP‐2 and Noggin expression was regulated using lentiviruses encoding short hairpin RNA and exogenous Noggin, respectively, which enabled evaluation of how this balance affected osteogenic differentiation of AS‐MSCs. Results: AS‐MSCs outperformed HD‐MSCs in osteogenic differentiation capacity. During osteogenic differentiation, AS‐MSCs secreted more BMP‐2 but less Noggin, accompanied by an overactivation of Smad1/5/8 and ERK‐1/2. When the Noggin concentration was increased or BMP‐2 expression was inhibited, the abnormal osteogenic differentiation of AS‐MSCs was rectified. In addition, the balance between BMP‐2 and Noggin secretion was restored. Conclusion: The results of this study demonstrate that an imbalance between BMP‐2 and Noggin secretion induces abnormal osteogenic differentiation of AS‐MSCs. These findings reveal a mechanism of pathologic osteogenesis in AS and provide a new perspective on inhibiting pathologic osteogenesis by regulating the balance between BMP‐2 and Noggin.